Differences in effects of varying compound extreme temperature and precipitation events on summer maize yield in North China - Zhongxian Liu; Rangjian Qiu; Qi Zhang (Agricultural Water Management)
With global climate change, compound extreme weather events are occurring more frequently in many parts of the world. Air temperature and precipitation are the most important weather elements that influence maize growth and yield formation, especially under rainfed cultivation. A consensus has developed that combined temperature and precipitation stresses cause more serious damage to crops than a single stress. However, differences in the effects of varying compound extreme temperature (hot or cold) and precipitation (dry or wet) events on maize yield remain unclear. Daily observations during the period 1991–2020 from 141 meteorological stations in North China were used to identify compound hot–dry, cold–dry, hot–wet, and cold–wet events during the summer maize growing season based on the standardized precipitation index (SPI) and standardized temperature index (STI). Three-dimensional joint cumulative probability distribution functions were constructed using vine copulas to assess the probability of yield loss rate (YLR) limited by different compound events. The results showed that the frequency and spatial extent of heat-related compound events in the 2010s were much higher than in previous decades, while those for compound cold-wet events were much lower. In contrast, there was no marked difference in the occurrence of cold–dry events among the different decades. Summer maize in North China has a higher probability of yield reduction with increases in temperature and precipitation stress, mainly because of increases in moderate and severe yield losses. Compared with heat or cold during the growing season, an increase in the severity of the dry or wet will lead to a more significant increase in the YLR, especially for compound cold–dry and cold–wet events. The occurrence of cold–wet and hot–dry events has a higher probability of being linked to severe yield loss than cold–dry and hot–wet events in North China. Our findings can assist decision-makers and growers in better understanding compound event occurrence characteristics and their potential effects on maize yield in North China, which is valuable for minimizing production risks.